2012
DOI: 10.1586/ern.12.49
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing essential tremor from Parkinson's disease: bedside tests and laboratory evaluations

Abstract: Distinguishing essential tremor from Parkinson’s disease can be challenging, both in the early stages of these diseases and as these diseases progress. Various tremor types (rest, postural, kinetic and intention) may be seen in both essential tremor and Parkinson’s disease. Furthermore, with time, the two diseases may coexist within a single patient. Detailed clinical examination with attention to specific features of tremor (frequency, amplitude, pattern and distribution) and associated neurological findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 69 publications
4
89
0
3
Order By: Relevance
“…23 As a result, Jain et al reported that # LD+DA, number of patients using both levodopa and dopamine agonists; LD, number of patients using only levodopa; DA, number of patients using only dopamine agonist. ## P+B, number of patients using both primidone and β-blockers; P, number of patients using only primidone; B, number of patients using only β-blockers.…”
Section: Discussionmentioning
confidence: 99%
“…23 As a result, Jain et al reported that # LD+DA, number of patients using both levodopa and dopamine agonists; LD, number of patients using only levodopa; DA, number of patients using only dopamine agonist. ## P+B, number of patients using both primidone and β-blockers; P, number of patients using only primidone; B, number of patients using only β-blockers.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, all the core features of PD (resting tremor, rigidity and bradykinesia) are more pronounced unilaterally at disease onset and generally persist asymmetrically throughout the course of the illness (Lee et al, 1995). In patients with ET, unilateral tremor is unusual and reportedly occurs at rates of 2-10%, depending on the criteria applied (Thenganatt and Louis, 2012). In patients with DT, unilateral presentation is common in focal forms, whereas bilateral presentation prevails in multifocal, segmental and generalized dystonia (Jedynak et al, 1991).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L I F Bove mentioning
confidence: 99%
“…Resting tremor is a cardinal feature of PD, occurring in 70-90% of patients. Although the reported prevalence of action tremor in patients with PD is as high as 88-92%, its amplitude is lower than that of resting tremor (Thenganatt and Louis, 2012). On the other hand, resting tremor occurs in 20-30% of patients with ET, even though it shows a lower amplitude than the action tremor seen in these patients (Cohen et al, 2003).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L I F Bove mentioning
confidence: 99%
“…Despite their potentially different origins, ET and PD frequently demonstrate similar symptoms and are often difficult to discriminate, especially at early stages. Up to 20% of patients with ET develop the signs typical for PD, whereas 30 to 50% of patients diagnosed with ET do not have ET [2,7,8].…”
Section: Introductionmentioning
confidence: 99%